Evaluating Intrusion Detection Approaches Using a Multi-criteria Decision Making Technique - I. , Ahmad (IJISCE, 2010)
We can witness the growing interest of researchers in the field of intrusion detection because a single attack can easily cause a big harm to the computer or network system. A number of intrusion detection approaches are available to tackle this issue but it is hard to identity that which approach is most suitable. Therefore, we have addressed this issue in this paper that which approach should be adopted in intrusion detection systems. The current paper explains the concepts, tools and methodologies being used to evaluate different intrusion detection approaches by a multi-criteria decision making technique such as Analytical Hierarchy Process (AHP). The present study indicates that artificial neural network approach is most suitable to tackle the current issues of intrusion detection systems such as regular updating, detection rate, false positive, false negative, suitability and adaptability